The ÓMICAS alliance, an international research program on multi-omics for crop breeding optimization - Jaramillo Botero, Andres; Colorado, Julian D.; Quimbaya, Mauricio; Rebolledo, María Camila; Lorieux, Mathias; Ghneim-Herrera, Thaura; Arango, Carlos A.; Tobón, Luis E.; Finke, Jorge; Rocha, Camilo; Muñoz, Fernando; Riascos, John J.; et al. (Frontiers Media, 2022)
The OMICAS alliance is part of the Colombian government’s Scientific Ecosystem, established between 2017-2018 to promote world-class research, technological advancement and improved competency of higher education across the nation. Since the program’s kick-off, OMICAS has focused on consolidating and validating a multi-scale, multi-institutional, multi-disciplinary strategy and infrastructure to advance discoveries in plant science and the development of new technological solutions for improving agricultural productivity and sustainability. The strategy and methods described in this article, involve the characterization of different crop models, using high-throughput, real-time phenotyping technologies as well as experimental tissue characterization at different levels of the omics hierarchy and under contrasting conditions, to elucidate epigenome-, genome-, proteome- and metabolome-phenome relationships. The massive data sets are used to derive in-silico models, methods and tools to discover complex underlying structure-function associations, which are then carried over to the production of new germplasm with improved agricultural traits. Here, we describe OMICAS’ R&D trans-disciplinary multi-project architecture, explain the overall strategy and methods for crop-breeding, recent progress and results, and the overarching challenges that lay ahead in the field.